Transformasi Pembayaran Digital : Optimalisasi QRIS bagi Pedagang UMKM di GBK Senayan - Astri Rumondang Banjarnahor; Ovi Hamidah Sari (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
In the digital era, the transformation of payment methods has become crucial to enhancing business efficiency and competitiveness, especially for street vendors in the Gelora Bung Karno (GBK) Senayan area. The implementation of the Quick Response Code Indonesian Standard (QRIS) among street vendors enables quick, safe, and simple digital transactions, supporting financial inclusion and reducing risks associated with cash handling. The QRIS awareness program conducted at GBK Senayan aimed to improve vendors' understanding of the benefits of digital payments, such as better financial management, reduced need for change, and increased security. This initiative included hands-on training, distribution of informative brochures, and direct practice to equip vendors with essential digital skills. As a result, 70% of vendors who participated in the program began using QRIS, and a positive shift in attitudes toward digital payment technology was observed. Primary challenges included limited technological understanding and unstable internet access; however, these can be addressed through ongoing technical support and assistance from technology service providers. With appropriate support, QRIS adoption among street vendors is expected to continue, enhancing competitiveness and ease for both vendors and consumers in the digital age.